Assertive speech acts in the YouTube Podcast Video “How Japanese people express our emotions with Ryoma” - Faishal, Najmi Muhammad; Saifudin, Akhmad (Japanese Research on Linguistics, Literature, and Culture, 2024)
This study aims to describe and analyze the functions of assertive speech acts in a YouTube podcast video titled "How Japanese People Express Our Emotions with Ryoma" uploaded on the Miku Real Japanese channel. The research employs a qualitative descriptive approach, using documentation techniques for data collection. The data examined consists of assertive utterances spoken by two speakers, Miku and Ryoma. Based on the analysis, five functions of assertive speech acts were identified in the video: stating (19 instances), informing (30 instances), reporting (9 instances), complaining (2 instances), and suggesting (1 instance). The most dominant function in this video is informing. The results of this study show that assertive speech acts are used in varied ways depending on the conversational context and reflect distinctive communication practices in Japanese culture. This research is expected to serve as a reference in the field of pragmatics, particularly in understanding language use in cross-cultural communication.